2003
DOI: 10.1111/j.1547-5069.2003.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Long‐Term Therapies: Evidence for Action

Abstract: The purpose of Forum is to promote contact, communication, and collaboration among scholars toward building knowledge for research and practice. I invite your contributions. Please send your statement about a significant problem related to health and illness and your questions, interests, or recommendations for nursing scholarly inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
389
1
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(414 citation statements)
references
References 0 publications
4
389
1
20
Order By: Relevance
“…Treatment adherence is acknowledged to be a major therapeutic goal in chronic disorders such as hypertension 32 and diabetes 33 . However, rates of compliance with long‐term treatments are far from optimal, with an average value of 50% 34 . Sub‐optimal treatment compliance has been also reported in immune‐mediated inflammatory diseases (IMIDs).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment adherence is acknowledged to be a major therapeutic goal in chronic disorders such as hypertension 32 and diabetes 33 . However, rates of compliance with long‐term treatments are far from optimal, with an average value of 50% 34 . Sub‐optimal treatment compliance has been also reported in immune‐mediated inflammatory diseases (IMIDs).…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 35 Several studies have shown that elderly survivors are more prone to low levels of adherence. 36 38 A systematic review which evaluated barriers to medication adherence identified patient related factors, such as the psychosocial profile, health beliefs, and health literacy. 38 …”
Section: Discussionmentioning
confidence: 99%
“…For children with ADHD, medication decisions are usually made by their parents, and so parent beliefs and attitudes toward ADHD are of critical importance. Charach and Fernandez further highlighted that parent beliefs about ADHD medication outweigh evidence of the real benefits and risks (33). It was found that parent beliefs and attitudes have more impact on medication use.…”
Section: Discussionmentioning
confidence: 99%